Effect of intermittent normobaric hypoxia exposure on acclimatization to high altitude by air induction - Bhaumik, Gopinath; Dass, Deepak; Ghosh, Dishari; Singh, Kishan; Reddy, Maram Prasanna Kumar (Asian Journal of Medical Sciences, 2021)
Background: In emergency like condition, defence personnel are deployed to high altitude without proper acclimatization. Maladaption at high altitude leads to high altitude illness like acute mountain sickness (AMS), high altitude pulmonary edema (HAPE) and high-altitude cerebral edema (HACE) which hampers the operational capabilities. Aims and Objectives: The aim of the present study was to assess the effect of intermittent normobaric hypoxia exposure (IHE) at sea level on different physiological responses during initial days of acclimatization at 3500m and 4000m altitudes in acute induction. Materials and Methods: The IHE subjects were exposed to 12% FIO2 (equivalent altitude 14500 ft) for 4 hrs/day for 4 consecutive days at sea level and 5th day they were inducted by air to 3500m altitude. Baseline recording of different physiological parameters like cardiovascular, respiratory, oxygen saturation and AMS score were measured at sea level as well as 3500m altitude on daily basis for 6 days to assess acclimatization status. To confirm acclimatization status at 3500m, on fifth day the IHE group subjects were transported by road to 4000m and again measured different basal physiological parameters (like cardiovascular, oxygen saturation and AMS score) for four consecutive days. Results: Different physiological parameters of IHE treated group were stabilized by day 4 of air induction at 3500m altitude. Whereas, at 4000m altitude, these parameters were stabilized by day 2 of induction. Conclusion: Acclimatization schedules of four days at 3500m and two days at 4000m are essential to avoid malacclimatization/or high-altitude illness.